Management of Weather and Climate Risk in the Energy Industry - Troccoli, Alberto. (NATO Science for Peace and Security Series C: Environmental Security, 2010)
Weather and climate information provide important elements in policy/decision making within the energy sector. Weather forecasts are employed routinely in the energy sector <U+0013> by energy producers through to suppliers, and by financial analysts through to national regulators <U+0013> to assist in decision-making. This information is used for diverse purposes such as the pricing of energy or the valuation of financial instruments. Climate information, including from seasonal to inter-annual predictions as well as climate change scenarios, is starting to be included in these decision processes. In addition, weather and climate information is naturally key in the development and use of renewable energy resources such as wind, solar and hydropower. Following an introductory section covering the production of weather and climate information (forecasts, re-analyses, and so on), and a second one dealing with policies for transferring information between the weather and climate sector and the energy industry, the book delves into multi-faceted applications within the energy industry, from the oil/gas sector to the renewable energy through to demand forecasting, thus providing an encompassing state-of-the-art picture of the interactions between weather, climate and energy. More on http://springer.com/978-90-481-3690-2 With contributions from: Dr Elena Akentyeva (Main Geophysical Observatory, Russia) Dr Alberto Arribas (UK Met Office) Mr Paolo Bonelli (CESI RICERCA S.p.A., Italy) Mr Mohammed S. Boulahya (ClimDevAfrica and Climate-Insight, Tunisia) Dr Carlo Buontempo (Met Office, UK) Dr Anca Brookshaw (Met Office, UK) Ms Hľn̈e Connor (HELIO International, France) Dr Laurent Dubus (Electricit ̌De France, France) Prof. John A. Dutton (Prescient Weather Ltd., USA) Ms Jane Ebinger (World Bank, USA) Dr Martin Fischer (Metnext, France) Dr Lizzie S. R. Froude (University of Reading, UK) Mr John Furlow (US Agency for International Development, USA) Ms Stefanie Greis (European Institute for Energy Research, Germany) Prof Robert J Gurney (University of Reading, UK) Ms Lucy Hancock (World Bank, USA) Dr Mike Harrison (Climate-Insight, UK) Mr Matteo Lacavalla (CESI RICERCA S.p.A., Italy) Mr Olivier Lemat̋re (Mťǒ-France, France) Dr Pascal Mailier (Royal Meteorological Institute of Belgium, Belgium) Dr Axel Michaelowa (University of Zurich, Switzerland) Ms Ulrike M<U+00fc>ller (European Institute for Energy Research, Germany) Mr Ken Mylne (Met Office, UK) Dr Oleg M. Pokrovsky (Main Geophysical Observatory, Russia) Dr Galina Rakitina (VNIIGAZ, Russia) Dr Benno Rothstein (Rottenburg University, Germany) Ms Jeannette Schulz (European Institute for Energy Research, Germany) Dr Alberto Troccoli (University of Reading, UK and CSIRO, Australia) Mr Vladimir Tsirkunov (World Bank, USA) Mr Sebastian Veit (African Development Bank, Tunisia) Dr Lada Vlasova (VNIIGAZ, Russia) Dr Lueder von Bremen (ISET e.V., Germany) Ms Laura E Williamson (HELIO International, USA)